Analisis Residu Pestisida pada Buah Tomat (Solanum lycopersicum) di Desa Sajen, Kecamatan Pacet, Kabupaten Mojokerto: Analysis of Pesticide Residues on Tomatoes (Solanum lycopersicum) in Sajen Village, Pacet District, Mojokerto Regency - Firmansyah, Lucky Dwi; Haryanta, Dwi; Susilo, Achmadi (Agrocentrum, 2025)
This study aims to analyze the pesticide residue levels in tomatoes (Solanum lycopersicum) marketed at Pasar Keputran, Surabaya, and to evaluate whether the residue content exceeds the maximum permissible limit set by applicable regulations.This study employs a quantitative method with laboratory experiments using gas chromatography-mass spectrometry (GC-MS) to analyze pesticide residues. The tomato samples tested were obtained from farmers in Desa Sajen, Pacet District, Mojokerto Regency, and sold at Pasar Keputran, Surabaya. The study grouped the samples based on the frequency of pesticide spraying: no spraying, one-time spraying, and two-time spraying. The results showed that pesticide residues were present in the tomatoes, with levels increasing as the frequency of spraying increased. Samples with two-time spraying contained residues exceeding the maximum permissible limits set by food safety regulations. Statistical analysis revealed significant differences between the residue levels in the samples and the expected values, indicating potential health risks for consumers. This study also highlights the importance of strict supervision of pesticide use, especially concerning dosage and frequency of spraying, to prevent negative impacts on public health. The implementation of safer and more sustainable agricultural practices is necessary to reduce the risk of excessive pesticide exposure and to raise farmers awareness of proper pesticide use procedures in accordance with standards.